A BIOLOGICAL MARKET ANALYSIS OF THE PLANT-MYCORRHIZAL SYMBIOSIS. (1st September 2014) - Wyatt, Gregory A. K.; Kiers, E. Toby; Gardner, Andy; West, Stuart A.
Abstract: It has been argued that cooperative behavior in the plant-mycorrhizal mutualism resembles trade in a market economy and can be understood using economic tools. Here, we assess the validity of this "biological market" analogy by investigating whether a market mechanism—that is, competition between partners over the price at which they provide goods—could be the outcome of natural selection. Then, we consider the conditions under which this market mechanism is sufficient to maintain mutualistic trade. We find that: (i) as in a market, individuals are favored to divide resources among trading partners in direct relation to the relative amount of resources received, termed linear proportional discrimination; (ii) mutualistic trade is more likely to be favored when individuals are able to interact with more partners of both species, and when there is a greater relative difference between the species in their ability to directly acquire different resources; (iii) if trade is favored, then either one or both species is favored to give up acquiring one resource directly, and vice versa. We then formulate testable predictions as to how environmental changes and coevolved responses of plants and mycorrhizal fungi will influence plant fitness (crop yields) in agricultural ecosystems.